2018
DOI: 10.1002/da.22864
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in resting-state functional networks among individuals with and without internalizing psychopathologies

Abstract: Background: Three well-established intrinsic connectivity networks (ICNs) involved in cognitive-affective processing include the cognitive control network (CCN), default mode network (DMN), and salience and emotional network (SEN). Despite recent advances in understanding developmental changes in these ICNs, the majority of research has focused on single seeds or networks in isolation with limited age ranges. Additionally, although internalizing psychopathologies (IPs), such as anxiety and depression, are ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 93 publications
1
11
0
1
Order By: Relevance
“…the DMN, VAN, and CCN) at age 16, (H2) with one biotype displaying RSFC patterns previously reported in relation to internalizing symptoms, e.g. heightened VAN-DMN and/or lower VAN-CCN (Burkhouse et al, 2019;Geng, Li, Chen, Li, & Gu, 2016;Scheuer et al, 2017). We further hypothesized that connectivity-based biotype would be a biomarker of internalizing problems throughout adolescence, where (H3) prior symptoms (age 14) would predict biotype status at age 16, (H4) current (age 16) problems would be associated with biotypes, and (H5) biotypes would predict future (age 18) internalizing problems (Prenoveau et al, 2011).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…the DMN, VAN, and CCN) at age 16, (H2) with one biotype displaying RSFC patterns previously reported in relation to internalizing symptoms, e.g. heightened VAN-DMN and/or lower VAN-CCN (Burkhouse et al, 2019;Geng, Li, Chen, Li, & Gu, 2016;Scheuer et al, 2017). We further hypothesized that connectivity-based biotype would be a biomarker of internalizing problems throughout adolescence, where (H3) prior symptoms (age 14) would predict biotype status at age 16, (H4) current (age 16) problems would be associated with biotypes, and (H5) biotypes would predict future (age 18) internalizing problems (Prenoveau et al, 2011).…”
mentioning
confidence: 89%
“…with internalizing psychopathologies, such as depression and anxiety (Burkhouse et al, 2019;Cullen et al, 2014;Roy et al, 2013). Given existing evidence, we expected that internalizing symptoms would be related both to aberrant connectivity within the DMN, VAN, and CCN, as well as differential connectivity between the networks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, despite a growing recognition that depression is a disorder of brain circuits (Williams, 2017), there are few longitudinal studies of the relation between within‐person changes in network function or structure and depression in adolescents. Although individuals with internalizing psychopathology (e.g., depression and anxiety) have been found to have age‐related alterations in functional network connectivity (Burkhouse et al, 2019), researchers have not yet related longitudinal within‐person changes in connectivity to changes in symptoms of depression over adolescence. Shapero et al (2019) found that abnormalities in CCN and DMN network connectivity predict the onset of depression in adolescence, suggesting that neural anomalies associated with depression are present even before clinical symptoms appear.…”
Section: Emerging Work and Future Directions: Toward A Precision Mentmentioning
confidence: 99%
“…Furthermore, although we corrected the analyses for age, we were, due to the complexity of the regression models (accounting for familial relationships), unable to take specific neurodevelopmental changes in functional connectivity into account. Previous work indicated changes within resting-state networks across the human lifespan [163] , [164] , [165] , while another study including typically developing individuals and patients with internalizing psychopathologies (age 7-29 years) indicated differential age-related alterations in iFC between the groups [169] . These findings stress the need for incorporating the neurodevelopmental perspective into endophenotype research (cf.…”
Section: Discussionmentioning
confidence: 97%